Hadis usûlü prensiplerinin kaynağı olarak kullanılan rivâyetler - Ölmez, Mustafa (My University, 2009)
Rivâyetin gerçek mahiyetini, şartlarını, çeşitlerini, hükümlerini, râvilerin durumlarını ve taşıması gereken özellikleri, rivâyet edebiyat çeşitlerini ve bütün bu konularla ilgili olarak hadîs âlimlerinin kullandığı ıstılahları inceleyen ilim dalı şeklinde tarif edilen hadîs usulünün prensipleri ortaya konulurken muhaddislerin bir takım yöntemler benimsediği bilinmektedir. Bu yöntemlerin en belirgini oluşturulan usûl prensipleri için ayet ve hadislerin delil olarak kullanımıdır. Muhaddisler, Kur’ân’ı Kerim ve Sünnetin zengin ve derin muhtevasından müstağni kalmaları mümkün olmadığı için, usûl kaidelerini tespit ederken gerek âyet gerekse de hadîsleri delil olarak kullanmışlardır. Doğrudan hadîs usûlü konusuyla ilgili olan âyet ve hadîsler, ilk hadîs usûlü müellifleri olarak kabul edilen Râmhürmüzî, Hâkim ve Hatîb’in eserlerine daha çok yansıdığı görülmektedir. Araştırmamız mezkûr müelliflerin konumuzla ilgili zikrettikleri rivayetlerin tespit, tahlil ve değerlendirmesinden ibarettir.

The Methodology of the Science of Hadith is defined to the be the science that investigates into the nature of reports on the authority of the Prophet, their specific conditions, varieties, status and the conditions of reporters, the properties required of them, the varieties of Hadith literature, and the terminology specific to this science. It is well known that Hadith scholars adopted methods specific to their subject-matter. For the methods concerning the principles of Hadith methodology, they identify supporting evidence from the Qur’an and the Prophetic traditions. Since Hadith scholars could not remain indifferent to the Qur’anic verses or the Prophetic sayings, they paid special attention to these religious sources when developing their methodology. Râmhurmuzî’s, Hâkim’s and Hatîb’s works—as these authors are among the primary authorities in Hadith methodology—feature many Qur’anic verses and Prophetic sayings in this regard. The M.A. thesis at your hand is dedicated to the identification, analysis and examination of the reports concerning the Hadith methodology in the above-mentioned works.
Keywords: İslam Dini_Hadis